2020
DOI: 10.6024/jmbai.2020.62.1.2114-03
|View full text |Cite
|
Sign up to set email alerts
|

Fish Consumption: Gauging the determinants of consumption and buying patterns across Kerala markets

Abstract: Fish marketing is an efficient economic production system which depends on several multi-level market functionaries from producers to consumers. The perfect model of fish market systems entails continuum in flow of the goods and services with high level of customer satisfaction. With this viewpoint, the current study was focused on analysing the different types of domestic fish markets across 14 districts of Kerala. The objective of the study is to quantify different market attributes such as type of domestic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, Huang et al [ 106 ] found that habit strength only influenced the behaviour of consuming fish indirectly via intention, indicating that habits were not formed due to occasional and irregular behaviour, which further indicates that consumers may have inadequate information or experience to make cognitive efforts in fish consumption decision-making. Further, studies have also indicated that purchasing habits, selection of specific fish species, and cooking and eating practices influence aquatic food consumption behaviour [ 125 , 126 , 127 , 128 ]. For instance, rural-to-urban migrants in Myanmar fried widely available farmed fish such as tilapia to integrate it into their daily diets instead of cooking small fish species such as anchovies or gourami [ Trichopodus pectoralis ] [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Huang et al [ 106 ] found that habit strength only influenced the behaviour of consuming fish indirectly via intention, indicating that habits were not formed due to occasional and irregular behaviour, which further indicates that consumers may have inadequate information or experience to make cognitive efforts in fish consumption decision-making. Further, studies have also indicated that purchasing habits, selection of specific fish species, and cooking and eating practices influence aquatic food consumption behaviour [ 125 , 126 , 127 , 128 ]. For instance, rural-to-urban migrants in Myanmar fried widely available farmed fish such as tilapia to integrate it into their daily diets instead of cooking small fish species such as anchovies or gourami [ Trichopodus pectoralis ] [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whether there can be economies of scale in this endeavour is a question that requires further deliberation. In another instance, we could also see that there are seldom substitute that satisfies the consumer in the absence of fish being available (Shyam, Monolisha, & Sunil 2020) [14] . With growing value-added production in fish products, there is an important segment that can be catered to whose strong preference for fish would lead them to consume products such as chutneys, pickles and powders.…”
Section: Introductionmentioning
confidence: 99%